2011
DOI: 10.1007/s11745-011-3630-5
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Lipogenic Enzymes in Peritumoral Adipose Tissue of Colorectal Cancer Patients

Abstract: Lipoprotein lipase (LPL) is the crucial enzyme for intravascular catabolism of triglyceride-rich lipoproteins. Fatty acid synthase (FAS) is a key anabolic enzyme that catalyzes the terminal steps in the novo biosynthesis of 18:2n-6. The involvement of both LPL and FAS in tumor biology has been widely demonstrated in different studies and to verify whether there are regional differences in the expression of these enzymes in visceral adipose tissue from patients with colorectal cancer might be representative of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…We have previously demonstrated that adipose and colon tissue interact, affecting the enzymatic activity of proteins involved in lipogenesis and cell proliferation [17]. Moreover, pronounced morphologic and molecular alterations of adipose tissue have been observed in tumor-bearing mice [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that adipose and colon tissue interact, affecting the enzymatic activity of proteins involved in lipogenesis and cell proliferation [17]. Moreover, pronounced morphologic and molecular alterations of adipose tissue have been observed in tumor-bearing mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pronounced morphologic and molecular alterations of adipose tissue have been observed in tumor-bearing mice [18]. Several studies have found a trophic effect of adipose tissue on colon cancer cell growth [17,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Further, the alterations in major components of the mTOR pathway like loss of function of PTEN , PI3K amplification/mutation and over-expression of S6K1 , 4EBP1 , eIF4E and AKT have been reported to be associated with many types of cancers, particularly in melanoma and glioblastama [55,56]. While, the decreased levels of lipogenic enzymes Lipoprotein lipase (LPL) and Fatty acid synthase (FAS), important components of the regulation of lipolysis in adipocytes pathway was reported to be associated with colorectal cancer [57]. …”
Section: Discussionmentioning
confidence: 99%
“…Decreased activity of fatty acid synthase and lipoprotein lipase was shown in adipose tissue of cancer patients [48] and adipogenesis, a process essential to form mature adipocytes, is impaired in experimental models of cancer cachexia with reduced expression of adipogenic transcription factors [44,49,50]. …”
Section: Cancer Cachexiamentioning
confidence: 99%